Sperm vs COVID-19: an unexpected case of male infertility (Portuguese Journal of Family Medicine and General Practice, 2025)
Introduction: Azoospermia is defined by the complete absence of spermatozoa in the ejaculate, resulting in the impossibility of conceiving with the male partner’s sperm. It is one of the most impactful forms of male infertility for couples. An increase in infertility cases reported after SARS-CoV-2 infection suggests a potential correlation between the virus and impaired spermatogenesis.Case description: A 42-year-old male, living with his wife and daughter, had a SARS-CoV-2 infection in 2022. He had no relevant past medical history or regular medication use. In January 2024, he consulted his family doctor (FD) due to secondary infertility, after 14 months of unsuccessful attempts to conceive, despite normal fertility studies in his wife. A spermogram revealed a complete absence of sperm and immature germ cells. A second analysis at a specialized clinic in March 2024 confirmed azoospermia. He was referred to urology, where further hormonal and ultrasound evaluations in May 2024 showed normal results. A testicular biopsy was suggested but refused by the patient. The couple decided not to pursue additional investigations or assisted reproduction techniques. At the follow-up appointment in July 2024, the FD offered psychological support due to the diagnosis’s potential emotional and social impact.Comment: Considering the patient's clinical history and current literature, SARS-CoV-2 infection appears to be the most plausible cause of his azoospermia. Although the couple has come to terms with the diagnosis, it remains a life-altering condition. This case highlights the critical role of the FD in providing not only clinical guidance but also emotional and psychological support and alternative options tailored to the couple’s preferences and needs.Introduction: Azoospermia is a medical condition defined by the total absence of spermatozoids in the sperm and by the impossibility of conceiving a pregnancy with those spermatozoids, being the type of infertility that affects the couple the most. Because of the increase in infertility cases described after SARS-CoV-2 infection, there seems to be a correlation between infertility and this type of infection.
Keywords: Azoospermia; COVID-19; Infertility; SARS-CoV-2